The last testament - Javerbaum, David (New York : Simon & Schuster, 2011)
Shares humorous observations, from God's perspective, on fatherhood while catapulting the gospels into modernity, covering everything from Adam and "Steve" and prayer in school to evolution and which Super Bowl teams to support.
Includes index.
Keywords: Religion -- Humor; God -- Humor; Religion -- Humor; God -- Humor